KASH training models: increasing levels of commitment and organizational effectiveness - Cabrera-Moya, Diego Rafael Roberto; Vasudevan, Hemaloshinee; Prieto-Rodriguez, Germán (Business: Theory and Practice, 2023)
The purpose of this article is to propose a strategic evaluation framework based on KASH training models, applicable in the first instance to SMEs in the clothing manufacturing sector in Bogota (Colombia), which in turn allows the possibility of developing new methodologies based on this proposal to be replicated in organisations from different sectors, as well as taking advantage of the possibility of increasing levels of commitment and motivation. The population of formal employees in this sector in 2021 was 626,350, and therefore the sample will be 384 employees. This framework is proposed as a set of postulates or tentative hypotheses in such a way that its approach becomes the support of a general framework and its subsequent verification through the analysis of the information collected in the sample about the perception of the relationship of the 4 KASH dimensions with commitment and organisational effectiveness. The main conclusion of this article proposes that each employer has differential expectations regarding the knowledge, skills, attitudes, and habits of employees and that, for this reason, the standard recruitment profiles must be complemented with adjusted training models that allow the use of the interaction of these 4 dimensions for the improvement of the levels of organisational effectiveness and commitment of the employees with the objectives of the firm.